Perlindungan Hukum bagi Konsumen Akibat Wanprestasi Penjual dalam Transaksi Jual Beli di E-Commerce - Hapsari, Diniar (LPPM Universitas Terbuka, 2024)
E-commerce is believed to have enormous potential to develop business volume in cyberspace. Apart from the many benefits felt by the public, the emergence of e-commerce transactions also creates problems. One of the problems that consumers often experience is that the goods ordered do not match the catalog photos in the e-commerce application. The problem that will be discussed in this research is how legal protection is for consumers for seller defaults in buying and selling transactions in e-commerce and the resolution of defaults for parties in buying and selling transactions in e-commerce. This research uses an empirical juridical approach where the data used is primary legal material and secondary legal material. Data was collected using the literature study method which was then analyzed qualitatively. From the research results, it is known that legal protection for consumers due to defaults committed by sellers can be found in Law Number 8 of 1999 and Law Number 11 of 2008. Apart from that, it can also be seen that the resolution if a business actor commits a default is that the consumer is entitled to receive responsibility in the form of compensation for defaults committed.